Responsibilities Of Notary In Tradding And Purchase Agreement (PPJB) In Semarang - Febrika Rizki Andini; Umar Ma'ruf (Jurnal Akta, 2018)
This study discussed how to be the responsibility of Notary to the authentic agreement making, which studied further is the Agreement of Tradding and Purchase Agreement. This study used sociological juridical analysis approach, with data obtained through literature and interviews, then the data were analyzed qualitatively. From the result of this study, it is agreed that the duties and authority of Notary by making a personal agreement which has been formed in Article 15 of Act No.30 Of 2004 concerning Notary Position. In this case, the notary is responsible for all agreements he/she has made. Agreement PPJB is made for the introduction and as a legal bridge to conduct the next legal screening, namely Agreement of Tradding and purchase to be read and signed in the vicinity of Notary. PPJB shall be made on the basis of the parties' persecution and prevention of default from either party. Because the Agreement of PPJB is an authentic agreement and made by or in the presence of a Notary then by itself the agreement becomes notary agreement. The power of its protection corresponds to the frequency of authentic agreements. The suggestion that can be given from this study is to further manage the Tradding and purchase agreement in Regulation, especially for the land issues. So that all parties used the Tradding and purchase agreement as engagement can be more secured.Keywords: Responsibility; Notary; Tradding and Purchase Agreement (PPJB).